Process Development of Sj-p80: A Low-Cost Transmission-Blocking Veterinary Vaccine for Asiatic Schistosomiasis - Molehin, Adebayo J.; Gray, Sean A.; Turner, Cheri; Davis, Jennifer; Zhang, Weidong; Khatoon, Sabiha; Rattan, Madison; Kernen, Rebecca; Peterson, Christopher; Sennoune, Souad R.; Carter, Darrick; Siddiqui, Afzal A. (Frontiers in Immunology, 2021)
Asiatic schistosomiasis caused by Schistosoma japonicum is a neglected tropical disease resulting in significant morbidity to both humans and animals - particularly bovines - in endemic areas. Infection with this parasite leads to less healthy herds, causing problems in communities which rely on bovines for farming, milk and meat production. Additionally, excretion of parasite eggs in feces perpetuates the life cycle and can lead to human infection. We endeavored to develop a minimally purified, inexpensive, and effective vaccine based on the 80 kDa large subunit of the calcium activated neutral protease (calpain) from S. japonicum (Sj-p80). Here we describe the production of veterinary vaccine-grade Sj-p80 at four levels of purity and demonstrate in a pilot study that minimally purified antigen provides protection against infection in mice when paired with a low-cost veterinary adjuvant, Montanide™ ISA61 VG. Preliminary data demonstrate that the vaccine is immunogenic with robust antibody titers following immunization, and vaccination resulted in a reduction of parasite eggs being deposited in the liver (23.4 – 51.4%) and intestines (1.9 – 55.1%) depending on antigen purity as well as reducing the ability of these eggs to hatch into miracidia by up to 31.6%. We therefore present Sj-p80 as a candidate vaccine antigen for Asiatic schistosomiasis which is now primed for continued development and testing in bovines in endemic areas. A successful bovine vaccine could play a major role in reducing pathogen transmission to humans by interrupting the parasitic life cycle and improving quality of life for people living in endemic countries.